PENGARUH PERBEDAAN KONSENTRASI EKSTRAK BIT MERAH DAN GELATIN TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK MARSHMALLOW BEET - Ann, Kho Chin; Suseno, Thomas Indarto Putut; Utomo, Adrianus Rulianto (Widya Mandala Surabaya Catholic University, 2012)
Marshmallow was known as snack food made from sugar, glucose syrup, gelatin and coloring with addition of high air contain that produce soft texture and melting sensation when it chewe. Thus, use of betalain pigment from red beet extract as natural colorant is attempted for marshmallow. The use of beet extract give pectin component and affect gelatin which act as foaming agent to form marshmallow texture. The differences of red beet extract and gelatin concentration will give some effect to the physicochemical properties and organoleptic of marshmallow beet. Red beet extract obtained from red beet bandung and commercial gelatin is used. The research design will be used is two factor Randomized Block Design, red beet extract concentration (5%, 10%, 15%) and gelatin concentration (3%, 4%, 5%) with three replications. The test results are analyzed by varians test (ANOVA) at α = 5% and Duncan’s Multiple Range Test at α = 5% if there is real influence. The result of the analysis: water content (21,41-24,35%), water activity (0,807-0,817), pH (7,09-7,32), density (0,4484-0,5401 gram/mL), texture (hardness (773,98-1599,25 g) and chewiness (774,04-1508,77 g)) color (lightness (46,2-60,4), redness (28,2-35,7) and yellowness (5,1-6,6)) and organoleptic (color (4,79-6,13), taste (4,92-6,06) and texture (4,36-6,30)).The best treatment of beet marshmallow is G3B1 treatment (5% gelatin concentration and 5% beet extract concentration), which has 21,41% water content, 0,811 water activity, 0,4790 g/mL density, 1599,25 g hardness, 1508,77 g chewiness, 6,04 lightness, 28,2 redness, 6,6 yellowness and the organoleptic 5,87; 5,84 6,30 for color, taste and texture.